2019
DOI: 10.5465/amp.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Shady Strategic Behavior: Recognizing Strategic Followership of Dark Triad Followers

Abstract: The importance of strategic behavior in organizations has long been recognized. However, so far the literature has primarily focused on leaders' strategic behavior, largely ignoring followers' strategic behavior. In the present paper, we take a follower trait perspective to strategic follower behavior, specifically focusing on how followers' Dark Triad traits (i.e., narcissism, Machiavellianism, and psychopathy) influence their strategic behavior. We argue that Dark Triad related strategic follower behavior is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 102 publications
0
21
0
Order By: Relevance
“…enable them to 'shine on a stage' (Nevicka, De Hoogh, Van Vianen, Beersma, & McIlwain, 2011;Schyns et al, 2019). We previously argued that the positive association observed between virtue signaling and narcissism may stem from narcissistic individuals' desire to display their alleged high moral character and behaviors, with the secondary aim of asserting their moral superiority over others.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…enable them to 'shine on a stage' (Nevicka, De Hoogh, Van Vianen, Beersma, & McIlwain, 2011;Schyns et al, 2019). We previously argued that the positive association observed between virtue signaling and narcissism may stem from narcissistic individuals' desire to display their alleged high moral character and behaviors, with the secondary aim of asserting their moral superiority over others.…”
Section: Methodsmentioning
confidence: 99%
“…The classical definition of narcissism emphasizes an individual’s highly inflated and unrealistically positive views of the self, and a motivation to assert their grandiose self-worth over others (Campbell & Foster, 2007; Morf, Horvath, & Torchetti, 2011). They are likely to make strategic choices that enable them to ‘shine on a stage’ (Nevicka, De Hoogh, Van Vianen, Beersma, & McIlwain, 2011; Schyns et al, 2019). We previously argued that the positive association observed between virtue signaling and narcissism may stem from narcissistic individuals’ desire to display their alleged high moral character and behaviors, with the secondary aim of asserting their moral superiority over others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature explores dark personality aspects in organisations, ( Schyns et al, 2019 ; Czarna and Zajas, 2020 ; Ray et al, 2020 ), career success ( Oflu et al, 2020 ) and leadership ( Van Scotter, 2019 ; Mackey et al, 2020 ; Syed et al, 2020 ). Spurk et al (2016) observed that narcissism as a dark personality trait is positively related to salary, Machiavellianism is positively related to leadership position, and career satisfaction while psychopathy is negatively related to career outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While there is also an interesting amount of research on different narcissist profiles based on Back et al's conceptualization (admiration vs. rivalry; 2013), we still know little about its implications in the workplace (for an exception, see Helfrich & Dietl, 2019). Schyns, Wisse, and Sanders (2019) suggested that followers with dark personality traits may use strategic behaviors to cause havoc in organizations, but what are the specific behaviors they use? What should organizations do to avoid hiring individuals with dark personality traits in the workplace?…”
mentioning
confidence: 99%